2007
DOI: 10.1007/s10633-007-9062-0
|View full text |Cite
|
Sign up to set email alerts
|

Pattern visual evoked potentials in Japanese patients with multiple sclerosis without history of visual pathway involvement

Abstract: A delay of the peak latency of the pattern visual evoked cortical potentials (pVEP) is accepted as one of the paraclinical evidence for a diagnosis of multiple sclerosis (MS). The purpose of this study was to evaluate the pVEPs in Japanese patients with MS without a history of visual pathway involvement. We studied the medical records of 29 MS patients without any history of visual pathway involvement, and with visual acuity correctable to > or = 20/20. The Goldmann visual fields, pupillary light reflexes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Some studies have suggested that the sensitivity of the technique may be as low as 25% in some circumstances, when, for example, computer monitors are used as stimuli, and can be normal in 40% to 50% of patients initially (1,32). The incidence of cases with abnormal cVEPs was also lower reported from Asia than that reported from Europe and the United States, and this difference was explained possibly due to racial differences and the use of different criteria (33).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the sensitivity of the technique may be as low as 25% in some circumstances, when, for example, computer monitors are used as stimuli, and can be normal in 40% to 50% of patients initially (1,32). The incidence of cases with abnormal cVEPs was also lower reported from Asia than that reported from Europe and the United States, and this difference was explained possibly due to racial differences and the use of different criteria (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is confirmed by the literature review. 1,2,1113 The most variable components were P50 and P200. The reason for the variability of component P50 was that the active electrode was placed at Oz, far after the retinal ganglion cells layer.…”
Section: Discussionmentioning
confidence: 99%
“…7-9 Atsushi Mizota ve ark. 10 görmesi tam ve muayenesi normal olan 29 MS hastasını dahil ettikleri çalışmada PVEP latansında uzama göstermişler ve istatiksel analizde kontrol grubuna göre anlamlı fark bulmuşlardı. Fakat amplitüdde gruplar arasında anlamlı bir fark gösterilememiştir.…”
Section: Discussionunclassified